Analisis Peningkatan Prestasi Belajar dan Kemampuan Berfikir Kreatif Mahasiswa Universitas Teknologi Mataram melalui Penerapan Focus Group Discussion - Umami, Satria (Lembaga Yasin AlSys, 2022)
The purpose of this study was to find out how to increase student achievement and creative thinking skills through the application of focus group discussions and to find out the supporting and inhibiting factors. In this study the data obtained in the field used observation, documentation and interview techniques. The research method used in this research is qualitative research with a case study approach with two data collection methods, namely primary data and secondary data, primary data by interviews and secondary data by collecting exam questions and quizzes during the lesson for one semester. books and archives of student grades related to research objectives. The results of this study indicate that there is still unsatisfactory relationship between the supporting lecturers and the students involved in learning, especially in class. Shows that students are still overwhelmed, confused in interacting with others.